The justification of God an exegetical and theological study of Romans 9:1-23 - Piper, John, 1946- (Grand Rapids, MI Baker, 1993)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Romans IX -- criticism, interpretation, etc